2022
DOI: 10.7759/cureus.21723
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pain Relief Approach for the Treatment of Multiple Dental Caries and Pulpitis

Abstract: Anxiety and stress toward treatment can hamper treatment completion in patients with dental caries and pulpitis. Therefore, effective management of post-treatment pain is important because poor pain management can lead to patient dissatisfaction. Ultrasound-guided nerve blocks provide good postoperative analgesia in maxillofacial surgeries. These surgeries can be performed under general or local anesthesia without complications. Here, we present the case of a patient with dental phobia who was successfully tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Sufficiently strong analgesia has been proven to be effective in surgery for malignant tumors and large-scale surgery for jaw deformity [ 29 , 30 ]. Our findings are consistent with those of a previous study, which demonstrated that favorable outcomes can be expected with sufficient analgesia even in dental caries treatment [ 26 ]. UGTNB can be expected to sufficiently improve the patient’s chief complaint of severe tooth pain due to pulpitis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Sufficiently strong analgesia has been proven to be effective in surgery for malignant tumors and large-scale surgery for jaw deformity [ 29 , 30 ]. Our findings are consistent with those of a previous study, which demonstrated that favorable outcomes can be expected with sufficient analgesia even in dental caries treatment [ 26 ]. UGTNB can be expected to sufficiently improve the patient’s chief complaint of severe tooth pain due to pulpitis.…”
Section: Discussionsupporting
confidence: 93%
“…Dentists are required to alleviate tooth pain due to pulpitis, which is the patient’s chief complaint. In the case of SMIP, the pain caused by pulpitis can be greatly reduced because pain relief is achieved with UGTNB [ 26 ]. The analgesic effect of UGTNB is strong and lasts for approximately 24-72 hours [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound-guided nerve blocks have been effectively used peri- or post-operatively. This analgesic method has many benefits compared with nonsteroidal antiinflammatory drugs and opioids [ 13 , 14 ]. UGTNB is applied in patients with maxillofacial fractures or those undergoing oral cancer surgery to exert a strong analgesic effect for approximately 24-72 h [ 14 ].…”
Section: Discussionmentioning
confidence: 99%